2004
DOI: 10.2320/matertrans.45.734
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Interfacial Reaction Layer on Reliability of CSP Joints Using Sn-8Zn-3Bi Solder and Ni/Au Plating

Abstract: In order to investigate the use of Sn-8Zn-3Bi solder as a potential substitute for Sn-Pb solder, which has a lower melting point than Sn-Ag family solders for CSP assembly, we studied mechanical properties of CSP joints plated with varying thicknesses of Au and Ni on Cu pad. Joint strength and other mechanical properties were evaluated in relation to reflow peak temperature. The combination of 0.05 mm Au plating thickness and reflow peak temperature of 498 K resulted in the best joint reliability in the as ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 5 publications
0
15
1
Order By: Relevance
“…Similar results have been observed in previous studies. 9,11) However, this result differs from that reported in other study. 23) Hwang et al studied the interfacial reaction between Sn-8Zn-3Bi solder and Au(0.1 mm)/Ni-8 mass%P plating layer at reflow temperature of 513 K, and reported that only a thin AuZn layer formed at the interface.…”
Section: Methodscontrasting
confidence: 57%
See 4 more Smart Citations
“…Similar results have been observed in previous studies. 9,11) However, this result differs from that reported in other study. 23) Hwang et al studied the interfacial reaction between Sn-8Zn-3Bi solder and Au(0.1 mm)/Ni-8 mass%P plating layer at reflow temperature of 513 K, and reported that only a thin AuZn layer formed at the interface.…”
Section: Methodscontrasting
confidence: 57%
“…13,14) Recently, compared with Sn-Ag solders, Sn-Zn solders have been highly recommended as a substitute for eutectic Sn-Pb solder due to their low melting point, excellent mechanical properties and low cost. 9,12) Eutectic Sn-9 mass%Zn solder has a melting temperature (471 K) which is relatively close to that of eutectic Sn-Pb solder (456 K), and this has enabled industries to use this alloy without having to replace their existing manufacturing lines or electronic components. 11,12) Nevertheless, there are several problems that need to be addressed in order to increase the practical use of this solder alloy, such as its inferior wettability, easy oxidation, micro-void formation and low reliability.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations